Pendidikan Keutamaan dengan Model Peran di Sekolah Kedokteran - Sintak Gunawan (Respons: Jurnal Etika Sosial, 2008)
Abstract: How does one become a good doctor? Can good character be taught? This questions should be asked through the learning process in medical education. The purpose of medical education is to transmit the knowledge, train the skills, and instill values, good characters, and behaviours. Medical schools have traditionally depended on good role models as part of an informal curriculum to inculcate professional values, attitudes, and behaviours in students and young doctors. I would like to explore the concept of role models in medical education, and taking compassion as an example of model.Kata Kunci: Dokter, pendidikan kedokteran, karakter, keutamaan, belaskasihan